2021
DOI: 10.1128/spectrum.00834-21
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Molecular Characteristics of Avian Pathogenic Escherichia coli in “No Antibiotics Ever” Broiler Farms

Abstract: Avian pathogenic Escherichia coli causes one of the most detrimental bacterial diseases to the United States poultry industry, colibacillosis. Colibacillosis leads to decreased performance, early mortality, and subsequent production loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Colibacillosis, caused by avian pathogenic E. coli in broilers, is characterised by lesions within the air sacs, the heart, and the liver, followed by septicaemia and death. Colibacillosis causes decreased performance, early (first week) morbidity and mortality (Guabiraba and Schouler, 2015 ; Fancher et al., 2021 ). Kemmett et al.…”
Section: Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Colibacillosis, caused by avian pathogenic E. coli in broilers, is characterised by lesions within the air sacs, the heart, and the liver, followed by septicaemia and death. Colibacillosis causes decreased performance, early (first week) morbidity and mortality (Guabiraba and Schouler, 2015 ; Fancher et al., 2021 ). Kemmett et al.…”
Section: Assessmentmentioning
confidence: 99%
“…Colibacillosis, caused by avian pathogenic E. coli in broilers, is characterised by lesions within the air sacs, the heart, and the liver, followed by septicaemia and death. Colibacillosis causes decreased performance, early (first week) morbidity and mortality (Guabiraba and Schouler, 2015;Fancher et al, 2021). Kemmett et al (2014) reported an overall flock mortality (flock of 25,700 birds) at point of slaughter of 4.36% while flock mortality in the first week was recorded as 1.03% and 0.44% for the first 72 h. Overall, 37 birds collected within 72 h after placement were collected and subjected to postmortem.…”
Section: Gastro-enteric Disorders and Infectious Diseasesmentioning
confidence: 99%
“…Respiratory diseases in poultry infected by E. coli are rising, leading to higher mortality rates, reduced production performance, and increased treatment costs for poultry, resulting in significant economic losses to the poultry farming industry ( Fancher et al, 2021 ). Mitigating this tissue damage and reducing the harm caused by the inflammatory response to the body has become a hot topic of current research.…”
Section: Introductionmentioning
confidence: 99%
“…The severely affected individuals exhibit unresponsiveness upon approach and show a lack of reaction to stimuli [ 2 ]. APEC is one of the most common bacterial pathogens that infect chickens, causing annual billion-dollar losses to the poultry industry worldwide, especially in antibiotic-free programs [ 3 , 4 , 5 ]. In “no antibiotics ever” broiler farms, 93% of samples, including litter samples, fecal samples, cloacal swabs, and tracheal swabs, were tested positive for E. coli , and 87.4% of all E. coli -positive samples were associated with APEC-like strains [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…APEC is one of the most common bacterial pathogens that infect chickens, causing annual billion-dollar losses to the poultry industry worldwide, especially in antibiotic-free programs [ 3 , 4 , 5 ]. In “no antibiotics ever” broiler farms, 93% of samples, including litter samples, fecal samples, cloacal swabs, and tracheal swabs, were tested positive for E. coli , and 87.4% of all E. coli -positive samples were associated with APEC-like strains [ 5 ]. The APEC isolates exhibit genetic similarities in virulence genes with human uropathogenic E.coli and neonatal meningitis E.coli , which could result in the development of urinary tract infections and meningitis in humans [ 6 ].…”
Section: Introductionmentioning
confidence: 99%